Rancang Alat Pengering Belimbing Wuluh (Averrhoa Bilimbi L) Tipe Lorong Menggunakan Sistem Blower Berbasis Arduino Mega2560 - Karo Karo, Riduansyah; Iskandar Iskandar; Zainal Arif (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Starfruit (Averrhoa bilimbi L.), commonly known in Indonesia as belimbing wuluh, is widely used as a natural acid in traditional cuisine. It is often processed into dried sour starfruit (asam sunti), which can last 1–1.5 years. However, traditional sun-drying methods are inefficient due to weather dependency, long processing times, and inconsistent product quality and color. This study aims to design and develop a tunnel-type starfruit dryer equipped with a blower system and heat control based on the Arduino Mega 2560. The research employs a quantitative method to evaluate tool performance. The dryer is cylindrical and supported by key components, including LPG gas as a heat source, a blower for air circulation, and a drum holder. Drying is conducted in six stages, each lasting 120 minutes, totaling 12 hours to achieve optimal dryness. Temperature monitoring at three points (T1, T2, T3) uses a MAX6675 sensor with a thermocouple connected to the Arduino Mega 2560, while weight measurement is done manually. Results indicate the tool functions effectively. A denser drying chamber and proper blower installation are recommended to ensure even heat distribution and improved drying efficiency for community use.